Identificación In - silico e In - vitro de genes housekeeping en raíces de Cecropia angustifolia (2024)
In order to contribute to the exploitation of the chemical potential of diversity in the tropical region of the Colombian Andes, the natural products research laboratory at Icesi University has been working with Cecropia angustifolia, focusing special attention on its pentacyclic triterpene acids (TPAs), which are recognized as its chemotaxonomic markers. However, the metabolic pathways in this particular genus have not been studied in depth, so analyses of the enzymatic processes for the production of its metabolites must be based on models corresponding to different species. These models are inherently variable given the differences between each species and C. angustifolia. Therefore, a process of understanding the plant's metabolic processes must begin with the identification of housekeeping genes (HK) that can serve as biological markers and provide a reliable reference for comparing gene expression under different environmental conditions and/or tissues. Thus, the objective of this project was to evaluate the genes encoding the GAPDH, ACT, and TUB proteins as possible housekeeping genes, using bioinformatics tools, molecular techniques, and in vitro cultures of C. angustifolia root tissues. To achieve this objective, a literature review of the GAPDH, ACT, and TUB genes present in species taxonomically close to C. angustifolia was conducted. Then, specific primers for each gene were designed using different bioinformatics tools, followed by in vitro validation using mRNA extracted from C. angustifolia tissues. The obtained results were verified by Sanger sequencing, which found the presence of molybdopterin biosynthesis protein and the TUB gene (β - tubulin) in the tissue sample used. The results reported in the present investigation require further depth and serve as a basis for future research on the characterization of HK genes in C. angustifolia.